Peran kepercayaan konsumen memediasi electronic word of mouth terhadap keputusan pembelian pada pengguna market place Lazada - Khatimah, Husnul; Salsabila, Safira (Jurnal STEI Ekonomi, 2023)
The purpose of this study was to examine the impact of EWOM on brand trust purchasing decisions of Lazada consumers. The variables examined in this study are EWOM, brand trust, and purchase decisions. Sample size drawn by distributing 100 respondents. The data collection method in this study was by questionnaire. The analytical technique used is MRA regression analysis. Based on the results of the analysis, EWOM has a positive and significant impact on consumer trust, EWOM has a positive and significant impact on purchasing decisions, and consumer trust has a positive and significant impact on purchasing decisions. It has made a significant impact and the role of consumer trust has been made clear. Key role in his EWOM mediation in marketplace product purchase decisions. Lazada in Bekasii city. Positive EWOM is one of our efforts to increase consumer confidence. EWOM has a significant impact on trust in product purchasing decisions. A positive EWOM encourages consumers to make immediate purchase decisions.